Teoría de la aplicacion de valoración de opciones: veinticinco años más tarde (1998)
The news from Stockholm that the prize in economic sciences had been given for option-pricing theory provided unique and signal recognition to the rapidly advancing but still relatively new discipline within economics wich relates mathematical finance theory and fiance practice.